Handbook of magnetic materials. - Buschow, K. H. J. (North-Holland, 1995)
Chapter one contains a detailed account of achievements on rare earth based artificial multilayered structures. The large body of experimental results that have become available for the many intermetallic compounds in which rare earths are combined with 3d transition metals is described in the second chapter. The ferrites form a large class of magnetic materials and some of these materials are of considerable technical importance. New results obtained on ferrites are described in chapter three, where the emphasis is on spinel ferrites. Previous volumes have contained chapters on the group of so called soft magnetic materials. Supplementary results dealing mainly with laminated amorphous alloys and electrical steels and the problem of the loss producing effect of the rotational magnetisation are highlighted in chapter four. Chapter five continues the updating process started in the previous volume of the basic magnetic interactions of rare earth intermetallics, dealing in particular with rare earth copper compounds of the type RCu2.